Analisis Kemampuan Pemecahan Masalah Berdasarkan Kemampuan Awal Dalam Pembelajaran Biologi Di Kelas X SMA Pembangunan Laboratorium UNP: (Analysis of Problem-Solving Ability Based on Prior Knowledge in Biology Learning in Grade of SMA Pembangunan Laboratorium UNP) - Marsel, Fanni Ochtaviana; Fadilah, Muhyiatul (BIODIK, 2025)
This study aims to examine students' abilities in solving problems based on their level of prior knowledge in biology learning, particularly on the topic of environmental changes. The research was conducted using a qualitative descriptive method and implemented in Grade X of SMA Pembangunan Laboratorium UNP during the odd semester of the 2024/2025 academic year. Data were collected through problem-solving tasks based on Polya’s (1973) indicators, which are divided into four stages: understanding the problem, devising a plan, carrying out the plan, and reviewing the solution.The observations showed that students' problem-solving abilities were generally categorized as low to very low, with an average achievement percentage across all indicators of 23.43%. Students experienced difficulties in fully understanding the problems, formulating relevant solutions, and developing logical and systematic steps for problem-solving. Furthermore, their ability to evaluate the solutions they had created was also not yet optimally developed.This condition is closely related to the students’ weak prior knowledge, which directly affects higher-order thinking processes such as reasoning and analysis. Therefore, these findings highlight the importance of strengthening prior knowledge as a foundation for improving the quality of problem-solving in biology learning. Abstrak. Penelitian ini bertujuan untuk mengkaji kemampuan peserta didik dalam menyelesaikan masalah berdasarkan tingkat kemampuan awal mereka dalam pembelajaran biologi terutama pada topik perubahan lingkungan. Penelitian ini dilakukan dengan metode deskriptif kualitatif yang diimplementasikan di kelas X SMA Pembangunan Laboratorium UNP pada semester ganjil tahun ajaran 2024/2025. Data diperoleh melalui pemberian soal pemecahan masalah berbasis indikator Polya (1973), yang terbagi menjadi empat tahap yaitu memahami masalah, merumuskan strategi penyelesaian, melaksanakan solusi, dan memverifikasi kembali jawaban. Hasil observasi menunjukkan bahwa kemampuan pemecahan masalah peserta didik secara umum tergolong rendah hingga sangat rendah, dengan rata-rata persentase capaian pada seluruh indikator sebesar 23,43%.Peserta didik menunjukkan kesulitan dalam memahami masalah secara menyeluruh, merumuskan solusi yang relevan, serta menyusun langkah-langkah penyelesaian yang logis dan sistematis. Selain itu, kemampuan mengevaluasi kembali solusi yang telah dibuat juga belum berkembang secara optimal. Kondisi ini berkaitan erat dengan kemampuan awal peserta didik yang lemah, yang berdampak langsung pada proses berpikir tingkat tinggi seperti penalaran dan analisis. Dengan demikian, temuan ini menegaskan pentingnya penguatan kemampuan awal sebagai fondasi untuk meningkatkan kualitas pemecahan masalah dalam pembelajaran biologi.